E-Service Quality and Customer Experience Impact on GoJek GoRide Customer Satisfaction in Bandar Lampung - Mutia Amalia; Dorothy Rouly Haratua Pandjaitan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research investigates how e-service quality and customer experience influence customer satisfaction among GoRide users in Bandar Lampung. The study is motivated by the growing reliance on online transportation services in Indonesia and the crucial role of customer satisfaction in fostering user loyalty. Employing a quantitative method with a survey design, data were gathered through questionnaires from 125 purposively selected respondents. The data were analyzed using multiple linear regression via SPSS. Findings indicate that both e-service quality and customer experience positively and significantly affect customer satisfaction, both individually and collectively. Key elements such as the app’s efficiency, security, and reliability, along with user experience factors like accessibility, promise fulfillment, and personalized service, are shown to be major contributors to the satisfaction of GoRide users in the area.